Haftungsinkompatible Kunststoff-Kunststoff-Verbunde mit gesteigerter Mediendichtheit mittels aufgesinterter Mikrostrukturen - Ott, Constantin; Wolf, Michael; Kleffel, Tobias; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2019)
For protection of electronic components against environmental influences, an innovative surface structuring process based on a sintered powder layer was investigated. The applied treatment process leads to micro undercuts on the insert surface, which can result in an increased bond quality and reduced leakage rates because of labyrinth sealing effects. With this new method, entire assemblies or specific components can be protected by manufacturing in assembly injection molding, which would enable the use of an efficient and mass production suitable process for assembly protection. The results clearly show that an increased pull out force level in combination with a reduced leakage rate can be achieved by means of micro structuring with a sintered powder layer.
Keywords: Adhesion incompatible; Assembly injection molding; Formfit; Media tightness; Micro-structuring; Undercut

In-situ leakage behavior of polymer-metal hybrids under mechanical load - Ott, Constantin; Drummer, Dietmar (International Polymer Processing, 2022)
Tightness against media is a frequent requirement for technical components. Despite various standardized test procedures, failure regularly occurs during use. Often, no clear cause for failure can be determined afterwards. In this article, a new test setup is presented and applied, which allows an in-situ measurement during a mechanical load. A flow meter with a measuring range of 0.02 mL/min to 5 mL/min is used for this purpose. This makes it possible to determine leakage rates with time resolution and thus to identify the moment of failure or the causal failure load. This new method was applied directly to different aluminum inserts with a polyamide 66 (PA66) overmold. It was shown that no increase in leakage occurs until a maximum force is reached, even with multiple loads. This maximum force depends only on the pretreatment of the inserts and can be determined in a simple pull-out test independently of the test setup used here and can therefore be used for the design of assemblies. In the test, a maximum force of 100 N was achieved for untreated inserts, 140 N for adhesion promoter-coated parts and 600 N for etched inserts with a contact area of 48 mm(2). With this results, a new link between adhesion and tightness can be shown, which of course is only valid for initial tight parts.
CRIS-Team WoS Importer:2022-10-14

Low-stress over-molding of media-tight electronics using thermoplastic foam injection molding - Ott, Constantin; Drummer, Dietmar (Polymer Engineering and Science, 2021)
Due to increasing automation and the associated rising demands on electronic assemblies, a suitable manufacturing process for large-scale production is needed to protect such products. The big challenge in this context is the low-stress encapsulation of the assemblies to protect them from external influences. In this study, the foam injection molding process was used to encapsulate FR4 (epoxy-based PCB) with Polyamid66 (PA66). The focus was on the production of a good assembly in terms of the quality of the bond and the media tightness. These parameters can be used to evaluate the protective effect against the surrounding. In the tests, a leakage rate of 0.025 m/min and shear stress of 6.5 MPa was achieved at low-foaming rates. This leakage is below the maximum acceptable threshold of 0.5 ml/min. The shear stress reaches values comparable to those in injection molding In addition to the requirements for leakage and composite quality, it could be shown that the internal mold pressure is reduced from 450 bar to below 10 bar by foaming. This can be used as the first indication of a reduced shear load on electronic components during over-molding. The suitability of the new solution concept is demonstrated.
CRIS-Team Scopus Importer:2021-03-05
Keywords: encapsulation; foam injection molding; media-tight; over-molding

Media-Tight Polymer-Polymer Assemblies By Means of Sintered Powder Layer in Assembly Injection Moulding - Ott, Constantin; Wolf, Michael; Drummer, Dietmar (Procedia Manufacturing, 2020)

Reducing component stress during encapsulation of electronics: a simulative examination of thermoplastic foam injection molding - Ott, Constantin; Drummer, Dietmar (Journal of Polymer Engineering, 2022)
The direct encapsulation of electronic components is an effective way of protecting components against external influences. In addition to achieving a sufficient protective effect, there are two other big challenges for satisfying the increasing demand for encapsulated circuit boards. The encapsulation process should be both suitable for mass production and offer a low component load. Injection molding is a method with good suitability for large series production but also with typically high component stress. In this article, two aims were pursued: first, the development of a calculation model that allows an estimation of the occurring forces based on process variables and material parameters. Second, the evaluation of a new approach for stress reduction by means of thermoplastic foam injection molding. For this purpose, simulation-based process data was generated with the Moldflow simulation tool. Based on this, component stresses were calculated with the calculation model. The suitability of the new approach was clearly demonstrated and a significant reduction in shear forces during overmolding was achieved. It was possible to demonstrate a process development that makes it possible to meet the two main requirements of direct encapsulation in addition to a high protective effect.
CRIS-Team Scopus Importer:2022-12-23
Keywords: encapsulation; foam-injection molding; simulation; stress reduction

Simulative study of polymeric core-shell foam particles for the enlargement of the material portfolio in 3-D high-frequency welding - Schneider, Kevin; Ott, Constantin; Drummer, Dietmar (Polymer Engineering and Science, 2021)
The steam chest molding process is currently state of the art concerning the generation of three-dimensional polymeric foam components made from particle foams. An adaption of the high-frequency welding process shows advantages regarding the required energy and the used water. Due to the low dielectric loss factors of the most common foam materials (PE, PP, and PS), they cannot be heated sufficiently by an electric field. To enable heating of these foams, the particles may be coated with a second material that shows a high dielectric loss. The possible heat development of the modified particles was simulatively investigated. To ensure a realistic simulation, the properties of the used materials are analyzed beforehand. The heating simulation shows clear dependence regarding the particle size and the shell thickness. By a suitable combination, sufficient heating is achievable. For single particles, an irregular temperature distribution is calculated, mainly caused by the difference of permittivity resulting in a local variation of electrical flux density. Bigger particles and thicker shells will result in faster heating ramps and higher overall temperatures. The additional calculation regarding a particle-particle interaction shows a homogenization of the temperature distribution across the particle surface.
CRIS-Team WoS Importer:2021-12-17